Channelizing Protected Farmer’s Varieties through Semi-Formal Seed Systems for Effective Utilization and Conservation of Agro-biodiversity: An Overview - RP SINGH; SUPRIYA SINGH; SANDEEP KUMAR LAL (Seed Research, 2026)
The paradigm of agricultural development based on maximizing grain yield in major cereal crops led to increased production of high-yielding wheat, and rice and replacement of other more nutrient-rich coarse cereals. The circulation of seed among farmers is central to agro-biodiversity conservation and dynamics. The local varieties (LVs) still cover significant area and virtually grown in all regions and seasons in India; the performance of farmers varieties (FVs)/ LVs is comparable under marginal conditions and even these varieties can out yield high yielding varieties (HYVs) under certain marginal environmental conditions. However, HYVs performed extremely well under favorable environmental conditions with high input and better management conditions and therefore, highly responsive to inputs. The low yield of FVs/LVs over modern varieties (MV’s) can be increased by a margin up to 20-25% by supplying quality seed of FVs alone. In the legal instrument (PPV&FR Act, 2001), farmers have been treated at par with formal breeders but the varieties developed by the former face difficulty to qualify for distinctiveness, uniformity and stability (DUS) tests, particularly in cross pollinated crops and therefore being marginalized. To take the full advantage of the rich genetic diversity in the form of FVs, an alternative registration and certification system developed by the food and agriculture organization of the United Nations known as Quality Declared Seed (QDS) system is advocated to channelize and commercialize FVs using formal system. The QDS is an alternative way to reach small and marginal farmers, who have limited access to certified seed for crop production; this system being semi-formal is less stringent and inexpensive as compared to conventional seed certification with the focus on local seed market. The semi formal seed systems are the needs of the day to provide the quality seed of FVs and indigenous/ under-utilized crops at local level in order to increase the resilience of the seed system for effective utilization and maintenance of agro biodiversity which is depleting at a faster pace. The semi-formal seed system may also serve as a bridge between formal and informal seed systems.